Ambulatory Blood Pressure Monitoring to Diagnose and Manage Hypertension - Huang, Qi-Fang; Yang, Wen-Yi; Asayama, Kei; Zhang, Zhen-Yu; Thijs, Lutgarde; Li, Yan; O'Brien, Eoin; Staessen, Jan A (Hypertension (Dallas, Tex. 1979), 2021)
This review portrays how ambulatory blood pressure (BP) monitoring was established and recommended as the method of choice for the assessment of BP and for the rational use of antihypertensive drugs. To establish much-needed diagnostic ambulatory BP thresholds, initial statistical approaches evolved into longitudinal studies of patients and populations, which demonstrated that cardiovascular complications are more closely associated with 24-hour and nighttime BP than with office BP. Studies cross-classifying individuals based on ambulatory and office BP thresholds identified white-coat hypertension, an elevated office BP in the presence of ambulatory normotension as a low-risk condition, whereas its counterpart, masked hypertension, carries a hazard almost as high as ambulatory combined with office hypertension. What clinically matters most is the level of the 24-hour and the nighttime BP, while other BP indexes derived from 24-hour ambulatory BP recordings, on top of the 24-hour and nighttime BP level, add little to risk stratification or hypertension management. Ambulatory BP monitoring is cost-effective. Ambulatory and home BP monitoring are complimentary approaches. Their interchangeability provides great versatility in the clinical implementation of out-of-office BP measurement. We are still waiting for evidence from randomized clinical trials to prove that out-of-office BP monitoring is superior to office BP in adjusting antihypertensive drug treatment and in the prevention of cardiovascular complications. A starting research line, the development of a standardized validation protocol for wearable BP monitoring devices, might facilitate the clinical applicability of ambulatory BP monitoring.